Comparative study on the effectiveness of case-based learning over small group discussion in pediatrics among 8th semester MBBS students - Santhakumari, Bindu Gopalakrishnan; Vijayan, Sini (International Journal of Research in Medical Sciences, 2024)
Background: Case based learning (CBL) is a new teaching learning method in medical education. The goal of this method of teaching is to prepare students for clinical practice through the use of authentic clinical cases. It links theory to practice through the application of knowledge to the cases. Hence it is effective for students who have already acquired foundational knowledge. The study was conducted to compare CBL and the traditional method of small group discussion (SGD) in Pediatrics among 8th semester MBBS students. Method: This quasi-experimental study was done among 8th semester MBBS students (n=83) of Government Medical College in south Kerala. The students were divided into two groups. One group was taught by CBL and the other by SGD. Pre-tests containing 10 multiple choice questions were conducted prior to each session. After three sessions, they were crossed over so that the two groups were exposed to both types of teaching learning methods. Post tests were conducted after 3rd (post test1) and 6th (post test2) sessions and the results were analysed. Results: There was no statistically significant difference in the post test scores between CBL and SGD groups (p value 0.696 for post test1 and p value 0.908 for post test2). However, the learners agreed that CBL had helped them in making concepts clear, stimulated active learning and improved their skills in case analysis. Conclusion: CBL can be used as a teaching learning method in Pediatrics to complement the traditional methods of teaching like SGD.